Factors That Affect Good Corporate Governance - Bayu Aji, Krisna; Hermawan, Aditya (International Journal of Educational Research & Social Sciences, 2022)
Research aims to determine the influence of leverage, profitability, company size, and company characteristics on good corporate governance. Research population of banking sub-sector companies listed on the Indonesia Stock Exchange in 2019-2020 with purposive sampling techniques. A sample of 31 companies. Types of quantitative research data and secondary data sources. Descriptive statistical data analysis techniques, classical assumption tests, multiple regression analysis, coefficients of determination and hypothesis tests. The results of leverage and profitability research affect good corporate governance, while the size of the company and the characteristics of the company have no effect on good corporate governance.